Tantangan Kebahasaan dan Budaya dalam Penerjemahan Bahasa Mandarin: Studi Kasus di Aceh - Destari, Dinda; Helmi, Rahil; Nurhidayah, Utin; Sandyaningrum, Juairiah Nastiti; Azhari, Azhari (Universitas 17 Agustus 1945 Surabaya, 2025)
This research is motivated by the fact that translators often face various difficulties in the process of translating from Mandarin to Indonesian and vice versa. The complexity of language and differing cultural contexts are the main factors affecting the accuracy and success of translation. The purpose of this study is to identify and describe the perceptions of translators in Aceh regarding the difficulties they face in translating Mandarin-language texts. This research uses a qualitative descriptive method with data collection techniques through interviews with several active translators residing and working in the Aceh region. The results of the study show that translators face various difficulties classified into two categories: intralingual and extralingual factors. Intralingual factors include difficulties in translating idioms and typical expressions, the use of slang, and the translator's limited knowledge of various topics or specific fields. Meanwhile, extralingual factors include illegible handwriting and the use of non-standard dialects by native Mandarin speakers, which often complicate the interpretation process. These findings provide a deeper insight into the contextual and cultural difficulties in Mandarin translation practice. Moreover, the results of this study are expected to serve as an important reference in the development of relevant translation training and curriculum in linguistically diverse regions such as Aceh, in order to enhance the competence and professionalism of translators.